Penyelesaian Sengketa Wakaf Melalui BASYARNAS - Jamaludin Jamaludin (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2019)
Each dispute must be resolved through an authorized institution. As a legal act, waqf management is a dynamic process that has the potential to cause dispute. The settlement of waqf disputes is carried out trough deliberation to reach consensus. If the settlement of the dispute is not succesful, the dispute can be resolved through mediation, arbitration, or court. If there is an arbitration clause, the court is not authorized to adjudicate the disputes of the parties who have been bound by the arbitration agreement.